Recoverability of Shipboard MVdc Architectures - Gudex, Jacob; Vygoder, Mark; Siddaiah, Rounak; Cuzner, Robert M (IEEE Energy Conversion Congress and Exposition, 2020)
Future shipboard electrical system designs, utilizing MVdc distribution, face many challenges. One of these challenges is designing a survivable system that can withstand faults, while maintaining quality of service during Fault Detection Isolation and Recovery (FDIR). Equipment implementations affect both the fault characterization and the system level recovery time. This work attempts to make topological comparisons as they relate to fault characterization and protection scheme planing in order to determine the minimum amount of energy storage needed to ride through an electrical fault.